Chiral Recognition of Proline Enantiomers by the Catalytic Oxygen Reduction and Formation of Cu(II)‐Polymer Complex Crystals. Issue 10 (18th September 2014) - Kim, Dong‐Min; Won, Mi‐Sook; Yoon, Jang‐Hee; Kim, Jung Ho; Goyal, Rajendra N.; Shim, Yoon‐Bo
Abstract A Cu(II)‐Poly(terthiophene carboxylic acid) (pTTC)/Nafion modified glassy carbon electrode has been used for the chiral recognition and discrimination of d‐ and l‐prolines by the catalytic oxygen reduction process and the shape of crystals formed on the electrode surface. The cyclic voltammetry with the modified electrode in the presence of oxygen recognized d‐ and l‐form of prolines by exhibiting a difference in the peak potential and the peak current of the oxygen reduction. The effect of pH and proline concentration on the peak current and the peak potential of oxygen have been studied. The SEM studies on the nature of crystals formed on a proline‐Cu(II)pTTC complex. The oxidation state of the copper species present at the electrode surface was characterized by ESCA.